Upaya Peningkatan Aktivitas dan Hasil Belajar Biologi melalui Model Pembelajaran Kooperatif Tipe Jigsaw bagi Siswa Kelas IX F Semester Ganjil SMP Negeri 8 Bandar Lampung - Junaidah, Elly (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2015)
Based on the results of observation on the odd semester XI F class of SMP Negeri 8 Bandar Lampung 2014/2015 in mind that learning process in the classroom is still using methods lectures so students tend to be passive. To resolve the issue, so researchers are looking for solutions to change the model of learning so that they can create an atmosphere of active learning, and improve learning outcomes i.e. cooperative learning model type with Jigsaw. The purpose of this research is to increase the activity and results of the study of biology students through the application of cooperative learning model type of Jigsaw. This research was carried out on the student class XI F class of Bandar Lampung on the odd semester lesson 2014/2015. This research was conducted in three cycles, each cycle consisting of 2 x meeting. Data collection techniques data obtained from the learning activities of students through observational learning. The data of this research consists of studying aspects of activity data: pay attention to the teachers explanation, discuss in groups, noting the results of the discussion and the timeliness of the discussion. Student learning outcomes data retrieved from the ultimate test on each end of cycle 1, 2 and 3 cycles. Data analysis activities by way of diskriptif. Data analysis the results of the study in a descriptive manner and percentage. The results of the analysis of the data shows that the model of cooperative learning, Jigsaw can increase the activity of the type as well as the results of learning biology students. The average percentage of students learning activities increased. From cycle 1, amounting to 12.06 (less active) to cycle 2 rose to 14.02 (less active), and increased again in cycle 3 of 16.08 (active). The average of the results of learning students also experience increased with the percentage comprehensively on cycle 1, of 69,27% to 72,10% (rising 8,42%) in cycle 2 and cycle 3 be 73,45% (rising 1.87%).